2017
DOI: 10.1016/j.molimm.2017.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Complement’s hidden arsenal: New insights and novel functions inside the cell

Abstract: A key component of both innate and adaptive immunity, new understandings of the complement system are expanding its roles beyond that traditionally appreciated. Evidence is accumulating that complement has an intracellular arsenal of components that provide not only immune defense, but also assist in key interactions for host cell functions. Although early work has primarily centered on T cells, the intracellular complement system likely functions in many if not most cells of the body. Some of these functions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
68
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(70 citation statements)
references
References 52 publications
2
68
0
Order By: Relevance
“…It remains unclear why cornea-infiltrating leukocytes express much lower levels of FcRn than is observed in circulating leukocytes (Fig. 8I, J); it tempting to speculate that leukocytes store antibody in circulation via FcRn-mediated retention for discharge upon activation and extravasation into inflamed tissues as they are proposed to do with soluble complement components (74). …”
Section: Discussionmentioning
confidence: 99%
“…It remains unclear why cornea-infiltrating leukocytes express much lower levels of FcRn than is observed in circulating leukocytes (Fig. 8I, J); it tempting to speculate that leukocytes store antibody in circulation via FcRn-mediated retention for discharge upon activation and extravasation into inflamed tissues as they are proposed to do with soluble complement components (74). …”
Section: Discussionmentioning
confidence: 99%
“…The activation of complement anaphylatoxins may not necessarily occur in the extracellular milieu and recent studies have substantiated the existence of intracellular stores of complement components and receptors ( e.g ., anaphylatoxin receptors and their ligands; C3b, factor B, factor H), which perform novel homeostatic and surveillance functions within human T cells 7,13,14 . A cell-intrinsic and functionally active complement system was anticipated more than 30 years ago by pioneering studies showing that human lymphocytes synthesize various complement components, regulators, and receptors 15,16 .…”
Section: Complement Regulation Of the Host Responsementioning
confidence: 99%
“…Complement components can be secreted locally by tissue-resident and infiltrating cells, while emerging evidence suggests the existence of an intracellular complement system with novel homeostatic and immune functions 2 . New insights into the mechanisms and locations of complement activation have revealed a new layer of complexity in the biology of complement and its impact on health and disease 7,8 . When dysregulated or overactivated due to host genetic or microbial virulence factors, complement can turn from a homeostatic to a pathological effector that drives various inflammatory disorders and cancer, which reflect the multifaceted nature of complement interactions 3,9 .…”
mentioning
confidence: 99%
“…Locally produced complements are known to play an important role in tissue homeostasis, and thus, dysfunction or dysregulation of the system may contribute to various diseases. Recent studies have shown that the complement system can also be activated inside the cell, and intracellular complement activation is known to be involved in many important cellular functions, including intracellular pathogen recognition/elimination, cytokine production, and metabolism (Arbore et al, ; Kolev & Kemper, ; Liszewski et al, ).…”
Section: Targeting the Complement System In Retinal Degenerative Disementioning
confidence: 99%